Evaluating a visual tool for systematic data collection and analysis for design students - S. Abd. Aziz, Madihah; Lindgaard, Gitte; Whitfield, T.W. Allan (Asian Research Publishing Network (ARPN), 2015)
In creating a successful product it is important to understand consumers’ perceptions of a product early in the design process. Often, design students lack the necessary data collection and user testing skills to support effective design decision-making. Consequently, their products might not be acceptable to the intended consumers and are thus likely to fail in the marketplace. For design students to acquire those skills, design curricula should incorporate statistical courses teaching the concepts of data and user testing. We addressed this challenge by developing an automated tool named DACADE, assisting design students to systematically collect and analyze data. This paper reports the user acceptance study of DACADE designed to determine its level of user satisfaction and aesthetic appeal. The results confirmed a need for a formal introduction to systematic sampling, collection of performance data as well as of opinion data, data analysis, interpretation, and application of statistics to product design.